Encouraging Trade and Foreign Direct Investment in Ukraine - Crane, Keith (RAND Corporation, 2007)
Reports on a study whose goal was to analyze Ukraine's environment for foreign trade and FDI and to develop policy proposals to expand Ukraine's foreign trade and attract more FDI, especially vis-à-vis the United States. Barriers to trade and FDI, the chief one being corruption, are described, and a two-pronged strategy for removing the worst barriers is recommended-one prong to bring immediate results; the other to set in motion changes requiring more time.